O18.5 Examining hpv prevalence and uptake of cervical cancer screening among hiv positive and negative women participating in a pilot rct in uganda comparing self-collection based hpv testing to via. (13th September 2015) - Mitchell, S; Moses, E; Pedersen, H; Sekikubo, M; Mwesigwa, D; Singer, J; Biryabarema, C; Byamugisha, J; Money, D; Ogilvie, G
Abstract : Introduction: With innovations in cervical cancer prevention, researchers must define best practices for cervical cancer screening in diverse populations and contexts. This pilot RCT compares the standard of care in most resource constrained settings, visual inspection with acetic acid (VIA), to self collected sampling for detection of high risk human papillomavirus (HR-HPV) DNA. We compared HPV prevalence and uptake of screening among women living with HIV (WHIV) and HIV negative (HIV-) women who participated in the trial. Methods: The pilot RCT was conducted between April and June 2014 when 500 women were recruited by community outreach workers in Kisenyi and completed a survey for demographic and risk factors including self-identified HIV status. Women were randomised to self-collected HR-HPV testing or VIA screening at the local health unit. Women who were HPV positive were referred for VIA. Women who tested positive at VIA were provided treatment with cryotherapy at the same visit or referred for colposcopy. Uptake rates of screening and HPV status in WHIV vs HIV- women were compared using Chi-square or Fisher's exact test. Results: Uptake of self-collected HR-HPV testing was 95.5% (21/22) in WHIV and 99.6% (226/227) in HIV- women (p = 0.17). Among WHIV, 42.9% (9/21) were HPV positive compared to 28.3% (64/226) HIV- women (p = 0.25). A greater proportion of WHIV were infected with HPV genotype 16 or 18 (28.6%, 6/21) than HIV- women (5.3%, 12/226) (p = 0.004). All 9 WHIV who were HPV positive attended VIA follow up, compared to 24/64 HIV- women. In the VIA arm, 64.0% (16/25) WHIV attended screening compared to 46.7% (105/225) HIV- women (p = 0.23). Conclusion: Self-collection based screening had high uptake in WHIV and HIV- women, suggesting that this method is highly acceptable and improves access compared to VIA. As more WHIV were HR-HPV infected, there is additional benefit to providing this type of screening given their increased risk for cervical cancer. Disclosure of interest statement: None of the authors have any conflicts to declare.